Modulating the Molecular Packing and Nanophase Blending via a Random Terpolymerization Strategy toward 11% Efficiency Nonfullerene Polymer Solar Cells. Issue 21 (20th July 2017) - Chen, Shanshan; Cho, Hye Jin; Lee, Jungho; Yang, Yankang; Zhang, Zhi‐Guo; Li, Yongfang; Yang, Changduk
Abstract: Despite rapid advances in the field of nonfullerene polymer solar cells (NF‐PSCs), successful examples of random polymer‐based NF‐PSCs are limited. In this study, it is demonstrated that random donor polymers based on thieno[2′, 3′:5′, 6′]pyrido[3, 4‐ g ]thieno[3, 2‐ c ]isoquinoline‐5, 11(4 H, 10 H )‐dione (TPTI) containing two simple thiophene (T) and bithiophene (2T) electron‐rich moieties (PTTI‐T x ) can be promising materials for the fabrication of highly efficient NF‐PSCs. With negligible influence on optical bandgaps and energy levels, the crystalline behavior of PTTI‐T x polymers was modulated by varying the T:2T ratio in the polymer backbone; this resulted in the formation of different microstructures upon blending with a nonfullerene m ‐ITIC acceptor in NF‐PSCs. In particular, a PTPTI‐T70: m ‐ITIC system enabled favorable small‐scale phase separation with an increased population of face‐on oriented crystallites, thereby boosting the processes of effective exciton dissociation and charge transport in the device. Consequently, the highest power conversion efficiency of 11.02% with an enhanced short‐circuit current density of 17.12 mA cm −2 is achieved for the random polymer‐based NF‐PSCs thus far. These results indicate that random terpolymerization is a simple and practical approach for the optimization of a donor polymer toward highly efficient NF‐PSCs. Abstract : Over 11% efficiency random polymer‐based nonfullerene solar cell is realized on the donor family of PTPTI‐T x containing various thiophene/bithiophene ratios in the backbone. A small‐scale phase separation with an increased fraction of face‐on oriented crystallites observed in the PTPTI‐T70: m ‐ITIC blend enables efficient exciton dissociation and charge transport, thereby inducing a remarkably enhanced J SC of 17.12 mA cm −2 through this system.